Skycrane Igor Sikorsky's last vision - McKenna, John A. (Library of flight, 2010)
The Skycrane was the last creation of aircraft design pioneer Igor Sikorsky. The full Skycrane story, however, has never been told. It was a radical design that many thought would not be successful. This book is about the many people who helped Mr Sikorsky's Skycrane become successful.